Metodologia para análise térmica de um freio de Fórmula SAE - Salomão, Gabriel Duvra (Universidade Federal de São Carlos, 2022)
The brake design for a Formula SAE high-performance prototype involves the mechanical-structural and thermal development of the system components, especially the brake disc, to ensure superior performance, reliability and safety for the vehicle and the driver. Usually, teams from student competitions such as Formula SAE and Mini-Baja have wide access to the theory and different methodologies of mechanical design of the brakes. However, the information and theoretical tools for the study and thermal analysis of the braking system are, in addition to being more complex, more difficult to access, leading this design facet not conducted. Thus, the present study aimed to present a methodology that can be replicated in student prototype brake projects, to provide student designers with information for the thermal analysis of the vehicle brake, with success and failure criteria for the analyzed project. To this end, a theoretical literature review was conducted to assist in the thermal modeling and in the elaboration of the proposed project methodology. The OptimumLap software was used to simulate the prototype laps in a circuit, and the MATLAB and NX-Nastran were applicated in dynamic simulations that comprise the thermal analysis of the project. At the end of the paper, it was possible to define the design criteria, demonstrate the use of OptimumLap as a tool to obtain input data, and use the modeling of the MATLAB and NX-Nastran to generate the transient output data that allow the analysis and validation of the project. It was concluded, therefore, that the proposed methodology is sufficient to carry out a complete thermal analysis of the brakes of a Formula SAE.
Methodology for thermal analysis of a brake SAE formula
Keywords: Fórmula SAE; Finite Elements Method; Brake disc; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS